COVID-19 and the Brain: A Psychological and Resting-state Functional Magnetic Resonance Imagin (fMRI) Study of the Whole-brain Functional Connectivity - Niroumand Sarvandani, Mohammad; Sheikhi Koohsar, Javad; Rafaiee, Raheleh; Saeedi, Maryam; Seyedhosseini Tamijani, Seyedeh Masoumeh; Ghazvini, Hamed; Sheibani, Hossein (Basic and clinical neuroscience, 2023)
Introduction: Coronavirus-2019 (COVID-19) spreads rapidly worldwide and causes severe acute respiratory syndrome. The current study aims to evaluate the relationship between the whole-brain functional connections in a resting state and cognitive impairments in patients with COVID-19 compared to the healthy control group. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) and Montreal cognitive assessment (MoCA) data were obtained from 29 patients of the acute stage of COVID-19 on the third day of admission and 20 healthy controls. Cross-correlation of the mean resting-state signals was determined in the voxels of 23 independent components (IC) of brain neural circuits. To assess cognitive function and neuropsychological status, MoCA was performed on all participants. The relationship between rs-fMRI information, neuropsychological status, and paraclinical data was analyzed. Results: The COVID-19 group got a lower mean MoCA score and showed a significant reduction in the functional connectivity of the IC14 (P<0.001) and IC38 (P<0.001) regions compared to the controls. The increase in functional connectivity was observed in the COVID-19 group compared to the controls at baseline in the default mode network (DMN) IC00 (P<0.001) and dorsal attention network (DAN) IC08 (P<0.001) regions. Furthermore, the alternation of functional connectivity in the mentioned ICs was significantly correlated with the mean MoCA scores and inflammatory parameters, i.e. erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Conclusion: Functional connectivity abnormalities in four brain neural circuits are associated with cognitive impairment and increased inflammatory markers in patients with COVID-19.